1984
DOI: 10.1016/0014-5793(84)80255-0
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative characterization of pyrimidine dimer excision from UV‐irradiated DNA (excision capacity) by cell‐free extracts of the yeast Saccharomyces cerevisiae

Abstract: Cell-free extracts from wild-type yeast @AD+) and from rad mutants belonging to the R4D3 epistatic group (radl-1, rad2-1, rad3-1, rad4-1) contain activities catalyzing the excision of pyrimidine dimers (PD) from purified ultraviolet-irradiated DNA which was not pre-treated with exogenous UV-endonuclease. The level of these activities in cell-free extracts from rad mutants did not differ from that in wild-type extract and was close to the in vivo excision capacity of the latter calculated from the LDH (about lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1987
1987
1990
1990

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…The authors concluded that the radl, rad2, rad3, rad4, radlO, and radl6 mutants were not defective in the incision of UV-irradiated DNA, but suggested that the defect in these mutants might be at the level of postincisional excision events. Consistent with this interpretation, they subsequently reported that extracts of both wild-type and rcad mutant cells catalyzed the complete excision of pyrimidine dimers from UV-irradiated DNA in vitro (14). Remarkably, in both studies DNA was incubated with cell extracts in the presence of ethylenediaminetetraacetate, suggesting no requirement for divalent cation in the incision or excision reaction(s).…”
Section: Friedbergmentioning
confidence: 68%
“…The authors concluded that the radl, rad2, rad3, rad4, radlO, and radl6 mutants were not defective in the incision of UV-irradiated DNA, but suggested that the defect in these mutants might be at the level of postincisional excision events. Consistent with this interpretation, they subsequently reported that extracts of both wild-type and rcad mutant cells catalyzed the complete excision of pyrimidine dimers from UV-irradiated DNA in vitro (14). Remarkably, in both studies DNA was incubated with cell extracts in the presence of ethylenediaminetetraacetate, suggesting no requirement for divalent cation in the incision or excision reaction(s).…”
Section: Friedbergmentioning
confidence: 68%
“…Although one set of studies reported such an incising ability with cell-free extracts from wild-type cells, such an activity was also shown for the five most sensitive mutant strains (Bekker et al . 1980(Bekker et al . , 1984 .…”
Section: Saccharomyces Cerevisiaementioning
confidence: 99%